Physicochemical characterization, sensory analysis and bioactive composition of a functional drink made from golden gooseberry, soybean and stevia - Sopla Huaman, Fredy Roland (2023)
In recent years, the consumption of beverages has increased; however, the excessive consumption of processed and packaged foods with a high sugar content is detrimental to human health as it has led to an increase in various metabolic diseases, which is why it is essential to introduce into the food chain new options of beverages enriched with fruit pulp, rich in polyphenolic compounds and antioxidants. This research sought to develop a functional beverage based on soybean juice and aguaymanto pulp sweetened with stevia, for which nine treatments were formulated consisting of 70, 80 and 90% soybean juice, 30, 20 and 10% aguaymanto pulp and 0.08, 0.10 and 0.12% stevia, and their physicochemical characteristics, sensory acceptability and bioactive composition were evaluated. The results showed that treatment 3 presented the highest sensory acceptability by the panelists with a score of 3.39 and presented an antioxidant power = 51.4% and a total polyphenolic content = 7.35 mg GAE/g. Concluding that the beverage elaborated can be considered as a functional beverage with nutraceutical attributes.